Modeling of electromigration failure under pulsed current conditions in confined copper interconnect - Lin, Jingyuan. (2010)
The time to void nucleation and the time for void growth to failure were determined using a program code based in MATLAB environment under pulsed current conditions. The program code is a solution to a partial differential equation of a widely used Korhonen-Clement model. Based on the simulated results, for void nucleation, the duty cycle exponent, m, and the current density exponent, n, were evaluated to be 1.99 and 1.98, respectively. For void growth to failure, the m and n values were estimated to be 0.97 and 0.95. Both the m and n values evaluated for void nucleation and void growth follows the average current density model, which is a modified Black’s equation.